Pembelajaran Online dan Hasil Menulis Karangan Argumentasi di Era Big Data - Susi Alawiyah (Unversitas Muhammadiyah Mataram, 2020)
Abstract: This study aims to determine the effect of the application of online learning on the results of writing arguments at SMK Negeri 5 Tangerang district in the era of big data. This research is a descriptive quantitative research in which the process of extracting information is manifested in the form of numbers as a tool to find information about what is known. The study population was all 11th grade students of SMK N 5 Tangerang Regency. The sample of this research is the 11th grade students of TPM 1 and 11th grade of TPM 2. The descriptive statistical method is used to analyze the application of online learning and its effect on the results of writing arguments. The research was conducted in March and April 2020, data were obtained from questionnaires and assessments of the results of writing student argument essays. The results of this study indicate that the magnitude of the parameter coefficient (-0.065) means that there is a negative effect on the application of online learning and the t statistical value is 0.632 with a significance level of 5% = 1.84, so the t statistical value is smaller than t table. The conclusion is that the application of online learning has a negative effect on the results of writing arguments in the era of big data.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan pembelajaran online terhadap hasil menulis karangan argumentasi di SMK Negeri 5 kabupaten Tangerang di era big data. Penelitian ini adalah penelitian kuantitatif deskriptif dimana proses penggalian informasi diwujudkan dalam bentuk angka-angka sebagai alat untuk menemukan keterangan mengenai apa yang diketahui. Populasi penelitian adalah seluruh siswa kelas 11 SMK N 5 Kabupaten Tangerang. Sampel penelitian ini adalah siswa kelas 11 TPM 1 dan kelas 11 TPM 2. Metode statistic deskriftip digunakan untuk menganalisis penerapan pembelajaran online dan pengaruhnya terhadap hasil menulis karangan argumentasi. Penelitian dilaksanakan pada bulan Maret dan April 2020, data diperoleh dari kuesioner dan penilaian hasil menulis karangan argumentasi siswa. Hasil penelitian ini menyatakan bahwa besarnya koefisien parameter (-0.065) yang berarti terdapat pengaruh yang negatif penerapan pembelajaran online dan nilai t statistik sebesar 0.632 dengan taraf signifikansi 5% = 1.84 maka nilai t statistik lebih kecil dari t tabel. Kesimpulannya bahwa penerapan pembelajaran online berpengaruh negatif terhadap hasil menulis karangan argumentasi di era big data.